Winners and losers in the first generations after structural social security reform: the Uruguayan case - Forteza, Álvaro (2018)
In the 1990s, several Latin American countries privatized their social security schemes to a greater or lesser extent. The main reason for these reforms was the dearth of public PAYG systems. As yet, here is no consensus on how these reforms stand to affect pensions. We focus on the Uruguayan case, where the first generations of the new regime are due to retire soon. Some workers will receive lower pensions than those with similar income and labor histories but who retired under the «transitional» regime. Meanwhile, others will receive higher pensions. We present simulations to help understand the specifics of the problem and identify potential winners and losers.